Makna Dalâl dalam al-Qur’an Perspektif Teori Dilâlat al-Alfâz - Ahmad Fawaid (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2013)
The interpretation methodology of Koran always has significant development. No death of interpretation, because the interpretation methodology will develop agree with throb of people civilization and language development. A matter of fact, Koran is a guidance book for man with Arabic language. For example, dalâl. Although concept of dalâl was exist at Muhammed period, but there are many distortion and wrong conclution after Muhammed, and lost of essential meaning of dalâl. Some people or some community said that dalâl is used to tought that considered wrong or deviate on right way, in other opinion they said that dalâl just for unbeliever, polytheist, immoral in law, and the others. The difference opinion is none other than different interpretation method to word of dalâl. Because of that, the writer interested to analyze dalâl with semantic method. Because the writer is conviced about semantic will give some enticement concept of dalâl.